Video Animasi Promosi Kampus Universitas Mahakarya Asia Baturaja Menggunakan Adobe Animate 2021 - Agung Trilaksono; Suryanto (Universitas Mahakarya Asia, 2021)
An animated video was a series of images taken of a moving object. The image was then projected onto a screen, and loaded it at a certain speed to produce a live image. With the existence of Mahakarya Asia Baturaja University, which was arguably a new university, and information about Mahakarya Asia Baturaja University has not been widely spread, it was necessary to have an attractive promotion method for Mahakarya Asia Baturaja University. Therefore, the author tried to make a promotional animation video for the Mahakarya Asia Baturaja University Campus using Adobe Animated 2021 which was made in the form of a film entitled